An Online Seminar: Parenting Approaches for the Alpha Generation - Murti, Ade Iva; Musrah, Andi Tri Supratno; Arieq, Nadhief Amadda; Wandy, Wandy (Journal of Community Services: Sustainability and Empowerment, 2024)
The Alpha Generation, born from 2011 to 2025, is the most technologically advanced. This generation is generally proficient with technology but is also at risk of becoming addicted to devices and experiencing a decline in social interactions. To create a solid foundation, an educational strategy that involves family, schools, and the community is essential. Parents must adopt effective parenting strategies suitable for the Alpha Generation. This community service project aimed to educate and engage the community about the optimal parenting methods for Gen-Alpha online, encouraging greater participation over the weekend. The audience consisted of parents of seventh-grade students. The initiative took place online via Zoom with a public junior high school, SMP Negeri 174 Jakarta.